Reimagining a Lost Armenian Home: The Dildilian Photography Collection - Marsoobian, Armen (I.B. Tauris, 2017)
For nearly a century members of the Dildilian family practiced the art of photography in Ottoman Turkey, Greece and the United States. This book contains over 200 photographs, primarily from the Ottoman era, beginning with the creation of the family business by Tsolag Dildilian in Sivas in central Turkey in 1882 and concluding in 1922 in Samsun, when the family was forced into exile in Greece. The photographs and the stories that unfold around them capture a defining period in the nearly three thousand year history of the Armenians in Anatolia and the Armenian Highlands. The early-twentieth century witnessed the violent erasure of the Armenians from their historic homeland, with catastrophic effects for the Dildilian family and their community. Yet this was also a period of unprecedented educational, cultural and commercial development for the Armenians. The Dildilian family was intimately involved in the triumphs and tragedies of these years and this book, through its rich pictorial history, sheds unprecedented light on the real-life experiences of Armenians in the devastating years of the Armenian Genocide and beyond. It is an unusual and original contribution to the social history of the Near East.
Keywords: Dildilian family; Armenians; Pictorial works; Portraits; Armenia; dept.phi; faculty_collection

The computer revolution and the problem of global ethics - Gorniak-Kocikowska, K. (Computer Ethics, 2017)
The author agrees with James Moor that computer technology, because it is 'logically malleable', is bringing about a genuine social revolution. Moor compares the computer reVolution to the 'industrial revolution' of the late 18th and the 19th centuries; but it is argued here that a better comparison is with the 'printing press revolution' that occurred two centuries before that. Just as the major ethical theories of Bentham and Kant were developed in response to the printing press revolution, so a new ethical theory is likely to emerge from computer ethics in response to the computer revolution. The newly emerging field of information ethics, therefore, is much more important than even its founders and advocates believe. © John Weckert 2007. All rights reserved.
Journal Abbreviation: Comput. Ethics
Keywords: Computer ethics; Computer revolution; Global ethics; Industrial revolution; Printing revolution; Professional ethics; dept.phi